Bowel Resection and Ileotransverse Anastomosis as Preferred Therapy for 15 Typhoid Ileal Perforations and Severe Peritoneal Contamination in a Very Elderly Patient - Benjamin Momo Kadia; Desmond Aroke; Martin Hongieh Abanda; Tsi Njim; Christian Akem Dimala (Case Reports in Surgery)
Typhoid ileal perforation (TIP) is the most lethal complication of typhoid fever. Although TIP is a surgical emergency by consensus, there is still much controversy regarding the most appropriate surgical approach to be used. Bowel exteriorization and secondary closure are usually recommended for patients presenting late with multiple TIPs and heavy peritoneal soiling. We, however, discuss a unique case of an 86-year-old patient with 15 typhoid ileal perforations successfully treated with one-step surgery comprising bowel resection and ileotransverse anastomosis in a resource-constrained setting of Cameroon.